A Közép-Európai Duna-völgy történeti földrajzi jellemzői - Csüllög, Gábor (Közép-Európai Közlemények, 2012)
It is the diversity of land stretching along the Danube that makes up Central Europe’s characteristic geographical region. The river itself, running through the Carpathian basin, is a characteristic geographical entity as well as a significant link between the western and south-eastern parts of Central Europe. Its determinative historical and geographical features are as follows: common geographical space; spatial flows linking the spaces; characteristic Central European cultural spaces; state spaces separated by political events; mosaic-like ethnic spaces created by migration; dividing buffer spaces brought about by the interests of power politics. During the past millennium, a system of empires had been dominant, whereas independent small states had only existed for a limited time. Until the end of the 18th century, there had been mainly political clashes. It was not until the beginning of the 19th century that processes of ethnic separation had started as a result of attempts to develop a cultural identity. The beginning of the 20th century brought real opposition, which started off the formation of separate nation-states. Because of the idea of an independent culture, an independent state, and a private geographical space, serious clashes took place within the region. This process, which is older than a hundred years, goes against the precious heritage of the past millennium: the mosaic-like recipient ethnic structures, the shared history as well as the common cultural and religious space.